DEVELOPMENT OF SAFE METHODS FOR SERVICING TRANSFORMERS AT LOW AND MEDIUM HEIGHTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
IN this article, we will discuss the possibilities of using a suspended hydraulic unit to safely service oil-immersed transformers at high and low altitudes.